(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article is devoted to the problem of cyclus forming. Theoretical aspects, different components composing genre form of lyrical cyclus, the role of plotline, primary and secondary cycli are considered and characterized in the article. The author refers to the history of the genre. The lyrical cyclus is considered as a genre that arose in the early 20th century. The principles that underlie the genre form of lyrical cyclus, their development reflected in different approaches and reaserches are the object of analysis. Various cyclus forming principles, such as chronological and unchronological are considered. The problems of lyrical plotline, the process of turning prose to lyrics are the main aspects of the analysis. Similarity and difference of genre forms of lyrical cyclus and the book of poetry are described in details in the article.